Uji Proporsionalitas Debit Bangunan Bagi Tipe Numbak - Hidayah, Susi; Suhardjono, -; Dermawan, Very (Jurnal Irigasi, 2015)
Water distribution structure is the main distribution facility and has been an important part in the operation system of irrigation networks. Numbak configuration lay the secondary water distribution structure, tertiary water tapping structure, and control structures in a parallel position, so it is suitable to be applied for the proportional system. This type of water distribution structure has been recommended in Irrigation Planning Criteria-04 (revision 2013), however, the planning information is still inadequate. The placement of sill on the proportional water distribution structure that has been tested is placed before the peer’s divisor. This makes the position of the distributed flow located not in a critical condition so that the distributed flow is also not proportional. A series of physical tests to assess variations in the placement of sill by the pillars dividing position conducted on a model that has been created by the Experimental Station for Irrigation, Research Center for Water Resources, Ministry of Public Works, is the type of the proportion of 1:2:1. The test results show that the average proportion of the distribution of discharge at all the scenarios for the right channel, center, and left respectively was 0.82:2.4:0.78. Recommendations of use and placement of sill by the pillars divisor as input for the planning and building of this type are also found in this study.